Optical adhesive sheet
A solvent-free optical adhesive sheet with a photopolymer polymer and specific properties addresses the environmental and corrosion issues in flexible display panels, ensuring flexible deformability and effective iodine ion suppression.
Patent Information
- Application Number
- JP2023149738
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
Existing optical adhesive sheets for flexible display panels face challenges in reducing environmental impact due to solvent-based manufacturing processes and may not adequately prevent corrosion of wiring on pixel panels from iodine ions.
A solvent-free optical adhesive sheet with a photopolymer polymer as the base, having a shear storage elastic modulus of 100 kPa or less at 25°C, and specific resistance changes in high temperature and humidity tests, which suppresses the passage of iodine ions and reduces environmental impact.
The solvent-free adhesive sheet ensures high flexible deformability, effectively suppresses iodine ion corrosion of pixel panel wiring, and reduces environmental impact by eliminating solvent volatilization in the manufacturing process.
Smart Images

Figure 2025042675000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical pressure-sensitive adhesive sheet. [Background technology]
[0002] A display panel has a laminated structure including elements such as a pixel panel, a polarizing film, and a cover film. In the manufacturing process of a display panel, for example, an optically transparent adhesive sheet (optical adhesive sheet) is used to bond the elements included in the laminated structure.
[0003] Meanwhile, development of repeatedly foldable display panels for smartphones and tablet terminals is progressing. Specifically, a foldable display panel can be repeatedly deformed between a bent shape and a flat non-bent shape. In such a foldable display panel, each element in a laminated structure is made to be repeatedly foldable, and a thin optical adhesive sheet is used for bonding between such elements. An optical adhesive sheet for a flexible display panel such as a foldable display panel is described, for example, in the following Patent Document 1. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-111754 A Summary of the Invention [Problem to be solved by the invention]
[0005] The optical adhesive sheet of Patent Document 1 is manufactured as follows. First, a reaction solution containing a monomer component for forming an acrylic-based polymer, a thermal polymerization initiator, and a solvent is prepared, and then the acrylic-based polymer is formed by solution polymerization in the reaction solution. Next, a thermal crosslinking agent is added to the polymer solution containing the acrylic-based polymer to prepare a pressure-sensitive adhesive composition (solvent-based pressure-sensitive adhesive composition). Next, the pressure-sensitive adhesive composition is applied onto a release liner to form a coating film. Next, the coating film on the release liner is dried by heating to form a pressure-sensitive adhesive layer (drying process). Next, a crosslinking reaction of the base polymer by the thermal crosslinking agent is promoted in the pressure-sensitive adhesive layer by aging treatment. In this manner, an optical adhesive sheet is formed on a release liner. Thus, Patent Document 1 describes an optical adhesive sheet formed from a solvent-based pressure-sensitive adhesive composition.
[0006] However, in the drying step, a relatively large amount of solvent in the coating film evaporates outside the coating film, and an optical pressure-sensitive adhesive sheet that includes such a step in its production process is not preferable from the viewpoint of reducing the environmental load.
[0007] On the other hand, optical adhesive sheets for flexible display panels are required to have a high degree of flexibility and deformability that allows them to follow the adherend (elements of the laminated structure) when the device is deformed. However, in flexible display panels in which the wiring formation surface of the pixel panel and the polarizing film are bonded via a conventional optical adhesive sheet, the softer the optical adhesive sheet, the more likely the wiring on the surface of the pixel panel is to corrode. This is thought to be because the softer the optical adhesive sheet, the more easily iodine ions derived from the polarizing film can pass through the optical adhesive sheet (iodine ions corrode the wiring of the pixel panel).
[0008] The present invention provides an optical adhesive sheet that is suitable for reducing the environmental load and is also suitable for use in flexible display panels. [Means for solving the problem]
[0009] The present invention [1] includes an optical adhesive sheet having a first adhesive surface and a second adhesive surface opposite to the first adhesive surface, wherein the optical adhesive sheet is a solvent-free adhesive sheet containing a photopolymerized polymer as a base polymer, the optical adhesive sheet has a shear storage modulus of 100 kPa or less at 25°C, and a first rate of change in resistance (R1 / R0) of the aluminum plate in the first high temperature and high humidity test described below is 120% or less.
[0010] First high temperature and high humidity test: First, a polarizing film with a retardation layer having a protective layer of 20 μm, a first adhesive layer of 1 μm, a polarizer film of 5 μm, a second adhesive layer of 1 μm, a first retardation layer of 3 μm, a third adhesive layer of 1 μm, and a second retardation layer of 4 μm in this order in the thickness direction is prepared. Next, the first adhesive surface of the optical adhesive sheet is bonded to the second retardation layer side of the polarizing film with a retardation layer to obtain a film with an adhesive layer. Next, a film piece with an adhesive layer having a size of 40 mm x 40 mm is cut out from the film with an adhesive layer. Next, the adhesive layer side of the film piece with an adhesive layer is bonded to the center of a square aluminum plate of 45 mm x 50 mm x 1 mm in plan view to obtain a laminate. Next, the initial resistance value R0 of the aluminum plate in the laminate is measured. Next, the laminate is autoclaved for 15 minutes under conditions of a temperature of 50 ° C. and a pressure of 0.5 MPa. Next, the laminate is left to stand at room temperature for 1 hour. Next, the laminate is left to stand in a high-temperature and high-humidity environment for 120 hours under conditions of a temperature of 85°C and a relative humidity of 85%. Next, the resistance value R1 of the aluminum plate in the laminate is measured. Next, a first rate of change (R1 / R0) of the resistance value R1 relative to the initial resistance value R0 is calculated.
[0011] The present invention [2] includes the optical adhesive sheet described in the above [1], in which the second change rate (R2 / R0) of the resistance of the aluminum plate in the second high temperature and high humidity test described below is 150% or less.
[0012] Second high temperature and high humidity test: First, the laminate after the first high temperature and high humidity test is left in a high temperature and high humidity environment for 120 hours under conditions of a temperature of 85°C and a relative humidity of 85%. Next, the resistance value R2 of the aluminum plate in the laminate is measured. Next, a second change rate (R2 / R0) of the resistance value R2 relative to the initial resistance value R0 is calculated.
[0013] The present invention [3] includes the optical adhesive sheet according to the above [1] or [2], which has a shear storage modulus of 200 kPa or less at -20°C.
[0014] The present invention [4] has a moisture permeability of 700 g / m2 measured under conditions of 40°C and 92% relative humidity. 2 The optical adhesive sheet according to any one of [1] to [3] above, wherein the shelf life is 24 hours or less.
[0015] The present invention [5] includes an optical adhesive sheet according to any one of [1] to [4] above, having a Cd ion content of 5 mg / kg or less. Effect of the Invention
[0016] As described above, the optical adhesive sheet of the present invention is a solventless adhesive sheet containing a photopolymerization polymer as a base polymer. Such an adhesive sheet can be manufactured from a solventless adhesive composition. In the process of manufacturing an optical adhesive sheet from the solventless adhesive composition, a process of volatilizing and removing the solvent from the coating film of the composition is not required. Therefore, the optical adhesive sheet of the present invention is suitable for reducing the environmental load.
[0017] Moreover, as described above, the optical adhesive sheet of the present invention has a shear storage modulus of 100 kPa or less at 25° C. Such a soft optical adhesive sheet is suitable for ensuring a high degree of flexible deformation that can follow the deformation of an adherend to which the adhesive sheet is attached, and is therefore suitable for flexible display panel applications.
[0018] In addition, the optical adhesive sheet of the present invention has a first change rate (R1 / R0) of the resistance of the aluminum plate in the first high temperature and high humidity test described above of 120% or less. When such an optical adhesive sheet is used to bond a pixel panel and a polarizing film, it is suitable for suppressing the passage of iodine ions derived from the polarizing film and suppressing corrosion of the wiring on the surface of the pixel panel, and is therefore suitable for flexible display panel applications. [Brief description of the drawings]
[0019] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of an optical adhesive sheet of the present invention. [Diagram 2] Fig. 2 shows an example of a method for using the optical adhesive sheet of the present invention. Fig. 2A shows a step of attaching the optical adhesive sheet to a first adherend, Fig. 2B shows a step of joining the first adherend and the second adherend via the optical adhesive sheet, and Fig. 2C shows an aging step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] As shown in FIG. 1, an adhesive sheet 10 as an embodiment of the optical adhesive sheet of the present invention has a sheet shape with a predetermined thickness and extends in a direction (plane direction) perpendicular to the thickness direction. The adhesive sheet 10 has an adhesive surface 11 (first adhesive surface) and an adhesive surface 12 (second adhesive surface) opposite to the adhesive surface 11. FIG. 1 exemplarily shows a state in which release liners L1 and L2 are attached to the adhesive surfaces 11 and 12 of the adhesive sheet 10. The release liner L1 is in releasable contact with the adhesive surface 11. The release liner L2 is in releasable contact with the adhesive surface 12. The adhesive sheet 10 is an optically transparent adhesive sheet (optical adhesive sheet) arranged at a light passing portion in a flexible display panel. Examples of flexible display panels include foldable display panels and rollable display panels. The flexible display panel has a laminated structure including elements such as a pixel panel, a polarizing film, and a cover film. The pressure-sensitive adhesive sheet 10 is used, for example, to bond elements included in a laminate structure in the manufacturing process of a flexible display panel. The release liners L1 and L2 are each peeled off at a predetermined timing when the pressure-sensitive adhesive sheet 10 is used.
[0021] The adhesive sheet 10 is a solventless adhesive sheet containing a photopolymerized polymer as a base polymer. Such an adhesive sheet 10 is formed from a solventless adhesive composition containing a photopolymerized polymer. The adhesive sheet 10 has a shear storage modulus of 100 kPa or less at 25°C. The method for measuring the shear storage modulus is specifically as described below in relation to the Examples. Furthermore, the adhesive sheet 10 has a first change rate (R1 / R0) of the resistance of the aluminum plate in the first high temperature and high humidity test described below of 120% or less.
[0022] First high temperature and high humidity test: First, a polarizing film with a retardation layer is prepared, which has a protective layer with a thickness of 20 μm, a first adhesive layer with a thickness of 1 μm, a polarizer film with a thickness of 5 μm, a second adhesive layer with a thickness of 1 μm, a first retardation layer with a thickness of 3 μm, a third adhesive layer with a thickness of 1 μm, and a second retardation layer with a thickness of 4 μm in this order in the thickness direction. Next, the adhesive surface 11 of the adhesive sheet 10 is attached to the second retardation layer side of the polarizing film with a retardation layer to obtain a film with an adhesive layer. Next, a film piece with an adhesive layer having a size of 40 mm x 40 mm is cut out from the film with an adhesive layer. Next, the adhesive layer side of the film piece with an adhesive layer is attached to the center of a square aluminum plate with a size of 45 mm x 50 mm x 1 mm in plan view to obtain a laminate. In this laminate, the four sides of the aluminum plate and the four sides of the film with an adhesive layer are parallel to each other. Next, the initial resistance value R0 of the aluminum plate in the laminate (aluminum plate / adhesive layer derived from optical adhesive sheet / polarizing film) is measured. Specifically, the sheet resistance of the aluminum plate surface in the laminate is measured by an eddy current method in accordance with JIS Z 2316 (the same applies to the measurement of resistance values R1 and R2 described below). Next, the laminate is autoclaved for 15 minutes under conditions of a temperature of 50°C and a pressure of 0.5 MPa. Next, the laminate is left to stand at room temperature for 1 hour. Next, the laminate is left to stand in a high-temperature, high-humidity environment for 120 hours under conditions of a temperature of 85°C and a relative humidity of 85%. Next, the resistance value R1 of the aluminum plate in the laminate is measured. Next, the first change rate (R1 / R0) of the resistance value R1 relative to the initial resistance value R0 is calculated. More specifically, the method of the first high-temperature, high-humidity test is as described below in the examples.
[0023] As described above, the adhesive sheet 10 is a solventless adhesive sheet containing a photopolymerized polymer as a base polymer. Such an adhesive sheet 10 can be produced from a solventless adhesive composition. The solventless adhesive composition does not require a step of volatilizing and removing the solvent from the coating film of the composition in the process of producing the adhesive sheet 10 from the composition. Therefore, the adhesive sheet 10 is suitable for reducing the environmental load.
[0024] As described above, the adhesive sheet 10 has a shear storage modulus of 100 kPa or less at 25° C. Such a soft adhesive sheet 10 is suitable for ensuring a high degree of flexible deformation that can follow the deformation of an adherend to which the adhesive sheet 10 is attached, and is therefore suitable for flexible display panel applications.
[0025] In addition, the pressure-sensitive adhesive sheet 10 has a first change rate (R1 / R0) of the resistance of the aluminum plate in the first high-temperature, high-humidity test described above of 120% or less. When such a pressure-sensitive adhesive sheet 10 is used to bond a pixel panel and a polarizing film, it is suitable for suppressing the passage of iodine ions originating from the polarizing film and suppressing corrosion of the wiring on the surface of the pixel panel. Therefore, the pressure-sensitive adhesive sheet 10 is suitable for flexible display panel applications.
[0026] As described above, the pressure-sensitive adhesive sheet 10 is suitable for reducing the environmental impact and is also suitable for use in flexible display panels.
[0027] The shear storage modulus of the adhesive sheet 10 at 25°C is preferably 80 kPa or less, more preferably 60 kPa or less, and even more preferably 45 kPa or less, from the viewpoint of ensuring a high degree of flexible deformation that can follow the adherend when the adherend is deformed. The shear storage modulus of the adhesive sheet 10 at 25°C is preferably 20 kPa or more, more preferably 35 kPa or more, even more preferably 38 kPa or more, and even more preferably 40 kPa or more, from the viewpoint of suppressing the iodine ion permeability of the adhesive sheet 10. The shear storage modulus of the adhesive sheet is determined by dynamic viscoelasticity measurement described later in the examples. Methods for adjusting the shear storage modulus of the adhesive sheet 10 include, for example, selection of the type of base polymer in the adhesive sheet 10, adjustment of the molecular weight, and adjustment of the blending amount, and selection of the type of crosslinking agent and adjustment of the blending amount.
[0028] The shear storage modulus of the adhesive sheet 10 at -20°C is preferably 200 kPa or less, more preferably 150 kPa or less, even more preferably 130 kPa or less, and even more preferably 110 kPa or less, from the viewpoint of ensuring high flexibility and deformability of the adhesive sheet 10 in the low temperature range. The shear storage modulus of the adhesive sheet 10 at -20°C is preferably 40 kPa or more, more preferably 60 kPa or more, even more preferably 80 kPa or more, and even more preferably 90 kPa or more, from the viewpoint of ensuring cohesive strength of the adhesive sheet 10 in the low temperature range.
[0029] The shear storage modulus of the adhesive sheet 10 at 60°C is preferably 15 kPa or more, more preferably 20 kPa or more, even more preferably 25 kPa or more, and even more preferably 28 kPa or more, from the viewpoint of ensuring the cohesive force of the adhesive sheet 10 in high temperature regions. The shear storage modulus of the adhesive sheet 10 at 60°C is preferably 60 kPa or less, more preferably 50 kPa or less, and even more preferably 40 kPa or less, from the viewpoint of ensuring a high degree of flexible deformability of the adhesive sheet 10 in high temperature regions.
[0030] From the viewpoint of suppressing the above-mentioned corrosion of the wiring on the surface of the pixel panel, the first rate of change (R1 / R0) in the adhesive sheet 10 is preferably 110% or less, more preferably 105% or less, and even more preferably 103% or less. The first rate of change (R1 / R0) is, for example, 100% or more. For example, the first rate of change (R1 / R0) can be adjusted by reducing the content of low molecular weight components contained in the adhesive sheet 10.
[0031] In terms of inhibiting the above-mentioned corrosion of the wiring on the surface of the pixel panel, the pressure-sensitive adhesive sheet 10 has a second change rate of resistance (R2 / R0) of the aluminum plate in the second high-temperature, high-humidity test described below of preferably 150% or less, more preferably 130% or less, even more preferably 110% or less, and even more preferably 105% or less. The second change rate (R2 / R0) is, for example, 100% or more. The second change rate (R2 / R0) can be adjusted, for example, by reducing the content of low molecular weight components contained in the pressure-sensitive adhesive sheet 10. Examples include:
[0032] Second high temperature and high humidity test: First, the laminate (aluminum plate / adhesive layer derived from optical adhesive sheet / polarizing film) after the first high temperature and high humidity test is left in a high temperature and high humidity environment for 120 hours under conditions of a temperature of 85°C and a relative humidity of 85%. Next, the resistance value R2 of the aluminum plate in the laminate is measured. Next, the second change rate (R2 / R0) of the resistance value R2 relative to the initial resistance value R0 is calculated.
[0033] The moisture permeability of the pressure-sensitive adhesive sheet 10 measured under conditions of 40° C. and a relative humidity of 92% is preferably 700 g / m from the viewpoint of suppressing wetting of the pressure-sensitive adhesive sheet 10 in a humid environment and suppressing iodine ion mobility. 2 24h or less, preferably 600g / m 2 24h or less, more preferably 550g / m 2 ·24h or less. Methods for adjusting the moisture permeability of the adhesive sheet 10 include, for example, selecting the type of base polymer in the adhesive sheet 10, adjusting the molecular weight, and adjusting the blending amount. Selection of the type of base polymer includes selection of the type of side chain of the base polymer and adjusting the amount. Selection of the type of side chain of the base polymer includes adjustment of the length of the alkyl portion in the side chain, and selection of the type of functional group contained in the side chain and adjusting the amount. Methods for adjusting the moisture permeability of the adhesive sheet 10 also include selection of the type of additive other than the base polymer and adjusting the blending amount. The method for measuring the moisture permeability of the adhesive sheet 10 is as described below in relation to the examples.
[0034] The Cd ion content of the adhesive sheet 10 is preferably 5 mg / kg or less, preferably 3 mg / kg or less, and preferably 2 mg / kg or less, from the viewpoint of suppressing the mobility of iodine ions within the adhesive sheet 10. The Cd ion content of the adhesive sheet 10 is, for example, 0.0 mg / kg or more, 0.5 mg / kg or more, or 1 mg / kg or less. The Cd ion content can be reduced by using a material with a higher purity for each component for forming the adhesive sheet 10.
[0035] The adhesive sheet 10 is a sheet-like pressure-sensitive adhesive (solvent-free adhesive sheet) formed from a solvent-free adhesive composition. The adhesive sheet 10 (solvent-free adhesive composition) contains at least a photopolymerization polymer as a base polymer. The photopolymerization polymer is a polymer formed by a polymerization method in which a polymerization reaction of a polymerizable component is promoted by irradiation with active energy rays such as ultraviolet rays.
[0036] The base polymer (photopolymerized polymer) is an adhesive component that imparts adhesiveness to the adhesive sheet 10. The base polymer is preferably an acrylic polymer. The acrylic polymer is a copolymer of polymerizable components containing 50% by mass or more of an alkyl (meth)acrylate ester. "(Meth)acrylic" means acrylic and / or methacrylic.
[0037] The (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20. The (meth)acrylic acid alkyl ester may have a linear or branched alkyl group, or may have a cyclic alkyl group such as an alicyclic alkyl group.
[0038] Examples of (meth)acrylic acid alkyl esters having a linear or branched alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, and methyl (meth)acrylate. p) Isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (i.e., lauryl (meth)acrylate), isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, cetyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, and nonadecyl (meth)acrylate.
[0039] Examples of the (meth)acrylic acid alkyl ester having an alicyclic alkyl group include (meth)acrylic acid cycloalkyl ester, (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring, and (meth)acrylic acid alkyl ester having a tricyclic or higher aliphatic hydrocarbon ring. Examples of the (meth)acrylic acid cycloalkyl ester include (meth)acrylic acid cyclopentyl, (meth)acrylic acid cyclohexyl, (meth)acrylic acid cycloheptyl, and (meth)acrylic acid cyclooctyl. Examples of the (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring include (meth)acrylic acid isobornyl. Examples of (meth)acrylic acid alkyl esters having three or more aliphatic hydrocarbon rings include dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.
[0040] The (meth)acrylic acid alkyl ester is preferably an acrylic acid alkyl ester having an alkyl group having 3 to 15 carbon atoms, and more preferably at least one selected from the group consisting of n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), n-octyl acrylate (NOAA), and lauryl acrylate (LA).More preferably, BA and NOAA are used in combination, or 2EHA and LA are used in combination.
[0041] The proportion of the (meth)acrylic acid alkyl ester in the monomer components is preferably 55% by mass or more, more preferably 60% by mass or more, and even more preferably 80% by mass or more, from the viewpoint of appropriately exhibiting basic properties such as adhesiveness in the adhesive sheet 10. This proportion is, for example, 96% by mass or less or 99% by mass or less.
[0042] The monomer component may include a copolymerizable monomer that is copolymerizable with the (meth)acrylic acid alkyl ester. The copolymerizable monomer may include, for example, a monomer having a polar group. The polar group-containing monomer may include, for example, a hydroxy group-containing monomer, a carboxy group-containing monomer, and a monomer having a nitrogen atom-containing ring. The polar group-containing monomer is useful for modifying the acrylic polymer, such as introducing a crosslinking point into the acrylic polymer and ensuring the cohesive force of the acrylic polymer.
[0043] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. The hydroxyl group-containing monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA).
[0044] The proportion of the hydroxyl group-containing monomer in the monomer components is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, from the viewpoint of introducing a crosslinked structure into the acrylic polymer and ensuring the cohesive strength of the pressure-sensitive adhesive sheet. From the viewpoint of adjusting the polarity of the acrylic polymer (related to the compatibility of various additive components in the pressure-sensitive adhesive sheet with the acrylic polymer), the proportion is preferably 15% by mass or less, more preferably 12% by mass or less, and even more preferably 10% by mass or less.
[0045] Examples of carboxy group-containing monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0046] The proportion of the carboxyl group-containing monomer in the monomer component is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, from the viewpoints of introducing a crosslinked structure into the acrylic polymer, ensuring the cohesive force of the pressure-sensitive adhesive sheet, and ensuring the adhesive force of the pressure-sensitive adhesive sheet to the adherend. The proportion is preferably 3% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less, from the viewpoints of adjusting the glass transition temperature of the acrylic polymer and avoiding the risk of corrosion of the adherend by acid.
[0047] Examples of monomers having nitrogen atom-containing rings include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, and N-vinylisothiazole.Preferably, the monomer having nitrogen atom-containing ring is N-vinyl-2-pyrrolidone (NVP).
[0048] The proportion of the monomer having a nitrogen atom-containing ring in the monomer components is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more, from the viewpoints of ensuring the cohesive strength of the pressure-sensitive adhesive sheet and the adhesive strength of the pressure-sensitive adhesive sheet to the adherend. The proportion is preferably 10% by mass or less, more preferably 7% by mass or less, and even more preferably 5% by mass or less, from the viewpoints of adjusting the glass transition temperature of the acrylic polymer and adjusting the polarity of the acrylic polymer (related to the compatibility of various additive components in the pressure-sensitive adhesive sheet 10 with the acrylic polymer).
[0049] The monomer component may contain other copolymerizable monomers. Examples of the other copolymerizable monomers include acid anhydride monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, epoxy group-containing monomers, cyano group-containing monomers, alkoxy group-containing monomers, and aromatic vinyl compounds. These other copolymerizable monomers may be used alone or in combination of two or more.
[0050] The base polymer can be formed, for example, by photopolymerizing the above-mentioned monomer components. Photopolymerization can be, for example, photopolymerization by ultraviolet irradiation. A photopolymerization initiator is used as the polymerization initiator.
[0051] Examples of the photopolymerization initiator include a radical photopolymerization initiator, a cationic photopolymerization initiator, and an anionic photopolymerization initiator.
[0052] Examples of the radical photopolymerization initiator include an acylphosphine oxide photopolymerization initiator, a benzoin ether photopolymerization initiator, an acetophenone photopolymerization initiator, an α-ketol photopolymerization initiator, an aromatic sulfonyl chloride photopolymerization initiator, a photoactive oxime photopolymerization initiator, a benzoin photopolymerization initiator, a benzyl photopolymerization initiator, a benzophenone photopolymerization initiator, a ketal photopolymerization initiator, and a thioxanthone photopolymerization initiator.
[0053] Examples of the acylphosphine oxide photopolymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of the benzoin ether photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-1,2-diphenylethan-1-one. Examples of acetophenone photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of α-ketol photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of aromatic sulfonyl chloride photopolymerization initiators include 2-naphthalenesulfonyl chloride. Examples of photoactive oxime photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of benzoin photopolymerization initiators include benzoin. Examples of benzyl photopolymerization initiators include benzyl. Benzophenone photoinitiators include, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, and polyvinylbenzophenone. Ketal photoinitiators include, for example, benzyl dimethyl ketal. Thioxanthone photoinitiators include, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.The photopolymerization initiator may be used alone or in combination of two or more kinds. The photopolymerization initiator is preferably at least one selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,2-dimethoxy-1,2-diphenylethan-1-one, and 1-hydroxycyclohexyl phenyl ketone.
[0054] The amount of the photopolymerization initiator used (the total amount of the multiple photopolymerization initiators when multiple photopolymerization initiators are used) is, for example, 0.01 part by mass or more, preferably 0.03 part by mass or more, and more preferably 0.05 part by mass or more, relative to 100 parts by mass of the monomer component, and is, for example, 1 part by mass or less, preferably 0.5 part by mass or less, more preferably 0.3 part by mass or less, and even more preferably 0.2 part by mass or less.
[0055] The base polymer preferably has a crosslinked structure. Examples of methods for introducing a crosslinked structure into the base polymer include the following first and second methods. In the first method, a base polymer having a functional group capable of reacting with a crosslinking agent and a crosslinking agent are blended into an adhesive composition, and the base polymer and the crosslinking agent are reacted in an adhesive sheet. In the second method, a multifunctional compound (crosslinking agent) such as a multifunctional monomer is included in the monomer components forming the base polymer, and a base polymer having a branched structure (crosslinked structure) introduced into the polymer chain is formed by polymerization of the monomer components. These methods may be used in combination.
[0056] The crosslinking agent used in the first method includes, for example, a compound that reacts with functional groups (such as hydroxyl and carboxyl groups) contained in the base polymer. Examples of such crosslinking agents include isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, carbodiimide crosslinking agents, and metal chelate crosslinking agents. The crosslinking agents may be used alone or in combination of two or more.
[0057] In the first method, the amount of crosslinking agent is, from the viewpoint of ensuring the cohesive strength of the adhesive sheet 10, preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, even more preferably 0.05 parts by mass or more, relative to 100 parts by mass of the base polymer, and is preferably 3 parts by mass or less, more preferably 1 part by mass or less, even more preferably 0.5 parts by mass or less.
[0058] In the second method, the monofunctional monomer and the polyfunctional compound such as the polyfunctional monomer for introducing a crosslinked structure may be polymerized at once or in multiple stages. In the multi-stage polymerization method, the monofunctional monomer is first polymerized (preliminary polymerization), thereby preparing a prepolymer composition containing a partial polymer (a mixture of a polymer with a low degree of polymerization and an unreacted monomer). Next, a polyfunctional compound is added as a crosslinking agent to the prepolymer composition, and then the partial polymer and the polyfunctional compound are polymerized (main polymerization).
[0059] Examples of the polyfunctional compound include polyfunctional monomers and polyfunctional oligomers that contain two or more ethylenically unsaturated double bonds in one molecule. Examples of the polyfunctional monomer include polyfunctional (meth)acrylates.
[0060] Examples of the polyfunctional (meth)acrylate include difunctional (meth)acrylate, trifunctional (meth)acrylate, and tetrafunctional or higher polyfunctional (meth)acrylate.
[0061] Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, glycerin di(meth)acrylate, ethoxylated bisphenol A diacrylate (BPAEODE), and neopentyl glycol di(meth)acrylate.
[0062] Examples of trifunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(acryloyloxyethyl)isocyanurate.
[0063] Examples of tetrafunctional or higher polyfunctional (meth)acrylates include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0064] Examples of polyfunctional oligomers include urethane (meth)acrylate oligomers, polyester (meth)acrylate oligomers, polyether (meth)acrylate oligomers, polyol (meth)acrylate oligomers, epoxy (meth)acrylate oligomers, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate.
[0065] The polyfunctional compound as the crosslinking agent in the second method may be used alone or in combination of two or more kinds. As the polyfunctional compound, at least one selected from the group consisting of 1,6-hexanediol diacrylate (HDDA) and dipentaerythritol hexaacrylate (DPHA) is preferably used.
[0066] When a polyfunctional monomer is used as the polyfunctional compound, the amount of the polyfunctional monomer in the monomer component is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and even more preferably 0.05 parts by mass or more, per 100 parts by mass of the monofunctional monomer, from the viewpoint of ensuring the cohesive strength of the adhesive sheet 10. The amount of the polyfunctional monomer is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1 part by mass or less, per 100 parts by mass of the monofunctional monomer, from the viewpoint of ensuring the above-mentioned flexible deformation property of the adhesive sheet 10.
[0067] When a polyfunctional oligomer is used as the polyfunctional compound, the amount of the polyfunctional oligomer in the monomer component is preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.7 parts by mass or more, per 100 parts by mass of the monofunctional monomer, from the viewpoint of ensuring the cohesive strength of the pressure-sensitive adhesive sheet 10. The amount of the polyfunctional oligomer is preferably 8 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, per 100 parts by mass of the monofunctional monomer, from the viewpoint of ensuring the above-mentioned flexible deformation property of the pressure-sensitive adhesive sheet 10.
[0068] In the polymerization, a chain transfer agent may be used for the purpose of adjusting the molecular weight, etc. Examples of the chain transfer agent include α-thioglycerol, lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, 2,3-dimercapto-1-propanol, and α-methylstyrene dimer.
[0069] The weight average molecular weight of the base polymer is preferably 100,000 or more, more preferably 300,000 or more, and even more preferably 500,000 or more, from the viewpoint of ensuring the cohesive force in the pressure-sensitive adhesive sheet 10. The weight average molecular weight of the base polymer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.
[0070] The glass transition temperature (Tg) of the base polymer is preferably 0° C. or lower, more preferably −10° C. or lower, and even more preferably −20° C. or lower. The glass transition temperature is, for example, −80° C. or higher.
[0071] The glass transition temperature (Tg) of the base polymer can be determined by the following Fox formula (theoretical value). The Fox formula is a relational expression between the glass transition temperature Tg of a polymer and the glass transition temperature Tgi of a homopolymer of a monomer constituting the polymer. In the following Fox formula, Tg represents the glass transition temperature (°C) of a polymer, Wi represents the weight fraction of a monomer i constituting the polymer, and Tgi represents the glass transition temperature (°C) of a homopolymer formed from the monomer i. The glass transition temperature of a homopolymer can be determined by a literature value. For example, the glass transition temperatures of various homopolymers are listed in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999). On the other hand, the glass transition temperature of a homopolymer of a monomer can also be determined by a method specifically described in JP-A-2007-51271.
[0072] Fox formula 1 / (273+Tg)=Σ[Wi / (273+Tgi)]
[0073] The pressure-sensitive adhesive composition may contain a silane coupling agent. The content of the silane coupling agent in the pressure-sensitive adhesive composition is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, based on 100 parts by mass of the base polymer. The content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less.
[0074] The pressure-sensitive adhesive composition may contain other components as necessary, such as an ultraviolet absorbing agent and an antioxidant.
[0075] From the viewpoint of ensuring sufficient adhesion to the adherend, the thickness of the pressure-sensitive adhesive sheet 10 is preferably 5 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more. From the viewpoint of thinning the device in which the pressure-sensitive adhesive sheet 10 is used, the thickness of the pressure-sensitive adhesive sheet 10 is preferably 300 μm or less, more preferably 200 μm or less, even more preferably 100 μm or less, still more preferably 70 μm or less, and even more preferably 50 μm or less.
[0076] The total light transmittance of the pressure-sensitive adhesive sheet 10 is preferably 60% or more, more preferably 80% or more, and even more preferably 85% or more. The total light transmittance of the pressure-sensitive adhesive sheet 10 is, for example, 100% or less. The total light transmittance of the pressure-sensitive adhesive sheet 10 can be measured in accordance with JIS K 7375 (2008). The method for measuring the total light transmittance is specifically described below in relation to the examples.
[0077] The adhesive sheet 10 can be produced, for example, as follows.
[0078] A long release liner L1 is run in the length direction of the release liner L1, and the coating step, the first lamination step, the photocuring step, the peeling step, the heating step, and the second lamination step are sequentially performed (roll-to-roll process). The release liner L1 may be, for example, a plastic film having flexibility. Examples of the plastic film include a polyester film, a polyethylene film, and a polypropylene film. Examples of the polyester film include a polyethylene terephthalate (PET) film, a polybutylene terephthalate film, and a polyethylene naphthalate film. The thickness of the release liner L1 is, for example, 3 μm or more, and, for example, 200 μm or less. In this embodiment, the surface of the release liner L1 is subjected to a release treatment. From the viewpoint of production efficiency, the running speed of the release liner L1 is preferably 1.0 m / min or more, preferably 2.0 m / min or more, and preferably 3.0 m / min or more. The running speed of the release liner L1 is preferably 10 m / min or less, more preferably 7 m / min or less, and more preferably 5 m / min or less, from the viewpoint of ensuring a sufficient heating time in the heating step described below.
[0079] In the coating step, a solvent-free adhesive composition is applied to the release-treated surface of the release liner L1 to form a coating film. Examples of methods for applying the adhesive composition include roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating.
[0080] In the first lamination step, the release-treated surface of the release liner L2, one side of which has been treated with a silicone release agent, is laminated to the coating film on the first release liner. Examples of the release liner L2 include the plastic films mentioned above for the release liner L1.
[0081] In the photocuring step, the coating film between the release liners L1 and L2 is irradiated with ultraviolet (UV) rays to photocure the coating film and form a pressure-sensitive adhesive layer. Examples of light sources for UV irradiation include black lights, ultraviolet LED lights, high-pressure mercury lamps, and metal halide lamps. In this step, the irradiation intensity is, for example, 200 mW / cm. 2 or more, for example, 400 mW / cm 2 The cumulative amount of irradiation light is, for example, 1000 mJ / cm 2 or more, for example, 3000 mJ / cm 2 The following is the result.
[0082] In the peeling step, the release liner L2 is peeled off from the adhesive layer on the release liner L1, thereby exposing the adhesive layer on the release liner L1.
[0083] In the heating step, the pressure-sensitive adhesive layer (exposed) on the release liner L1 is dried, for example, in a hot air oven. In this step, the heating temperature is preferably 90° C. or higher, more preferably 100° C. or higher, and even more preferably 110° C. or higher, from the viewpoint of effectively volatilizing unreacted low-molecular-weight components in the pressure-sensitive adhesive layer. The heating temperature is preferably 170° C. or lower, more preferably 150° C. or lower, and even more preferably 130° C. or lower, from the viewpoint of avoiding heat curing of the pressure-sensitive adhesive layer. The heating time is preferably 1 minute or longer, more preferably 3 minutes or longer, and even more preferably 5 minutes or longer, from the viewpoint of sufficiently volatilizing unreacted low-molecular-weight components in the pressure-sensitive adhesive layer. The heating time is preferably 10 minutes or shorter, more preferably 5 minutes or shorter, and even more preferably 3 minutes or shorter, from the viewpoint of production efficiency.
[0084] In the heating step, the first heating and the second heating, which are different in heating temperature, may be carried out in sequence. The temperature of the first heating (first heating temperature) is preferably 90° C. or higher, more preferably 100° C. or higher, and even more preferably 110° C. or higher, from the viewpoint of effectively volatilizing the unreacted low molecular weight components in the adhesive layer. The first heating temperature is preferably 170° C. or lower, more preferably 150° C. or lower, and even more preferably 130° C. or lower, from the viewpoint of avoiding heat curing of the adhesive layer. The time of the first heating (first heating time) is preferably 1 minute or more, more preferably 3 minutes or more, and even more preferably 5 minutes or more, from the viewpoint of sufficiently volatilizing the unreacted low molecular weight components in the adhesive layer. The first heating time is preferably 10 minutes or less, more preferably 5 minutes or less, and even more preferably 3 minutes or less, from the viewpoint of production efficiency. The temperature of the second heating (second heating temperature) is preferably lower than the first heating temperature, from the viewpoint of avoiding heat curing of the adhesive layer. The second heating temperature is preferably 70°C or higher, more preferably 80°C or higher, and even more preferably 85°C or higher, from the viewpoint of effectively volatilizing unreacted low molecular weight components in the adhesive layer. The second heating temperature is preferably 130°C or lower, more preferably 110°C or lower, and even more preferably 100°C or lower, from the viewpoint of avoiding heat curing of the adhesive layer. The second heating time (second heating time) is preferably 1 minute or longer, more preferably 3 minutes or longer, and even more preferably 5 minutes or longer, from the viewpoint of sufficiently volatilizing unreacted low molecular weight components in the adhesive layer. The second heating time is preferably 10 minutes or shorter, more preferably 5 minutes or shorter, and even more preferably 3 minutes or shorter, from the viewpoint of production efficiency.
[0085] In the second lamination step, the release-treated surface of a new release liner L2, one side of which has been treated with a silicone release agent, is laminated to the pressure-sensitive adhesive layer on the release liner L1.
[0086] In this manner, the pressure-sensitive adhesive sheet 10 with double-sided release liner can be produced. The manufacturing process of the pressure-sensitive adhesive sheet 10 does not require a step of volatilizing and removing the solvent from the coating of the pressure-sensitive adhesive composition. Therefore, the pressure-sensitive adhesive sheet 10 is suitable for reducing the environmental load.
[0087] 2A to 2C show an example of a method of using the adhesive sheet 10. FIG.
[0088] In this method, first, as shown in Fig. 2A, the adhesive sheet 10 is attached to one surface of a member 21 (adherend) in the thickness direction H. The member 21 is, for example, a pixel panel for a flexible display panel. Through this process, the adhesive sheet 10 for bonding to another member is provided on the member 21.
[0089] 2B, the member 21 and the member 22 are joined together via the adhesive sheet 10 on the member 21. The member 22 is, for example, a polarizing film for a flexible display panel.
[0090] Next, as shown in Fig. 2C, the adhesive sheet 10 between the members 21 and 22 is aged. Aging enhances the bonding strength between the adhesive sheet 10 and the members 21 and 22. The aging temperature is, for example, 20°C to 160°C. The aging time is, for example, 1 minute to 21 days. When the aging is performed by autoclaving (heating and pressurizing), the temperature is, for example, 30°C to 80°C, the pressure is, for example, 0.1 to 0.8 MPa, and the treatment time is, for example, 15 minutes or longer.
[0091] As described above, the adhesive sheet 10 has a shear storage modulus of 100 kPa or less at 25°C. Therefore, the adhesive sheet 10 between the members 21, 22 is suitable for ensuring a high degree of flexible deformability that can follow the members 21, 22 when the members 21, 22 are deformed. In addition, the adhesive sheet 10 has a first change rate (R1 / R0) of the resistance of the aluminum plate in the first high temperature and high humidity test described above of 120% or less. When such an adhesive sheet 10 is used to bond a pixel panel and a polarizing film, it is suitable for suppressing the passage of iodine ions derived from the polarizing film and suppressing corrosion of the wiring on the surface of the pixel panel. Therefore, the adhesive sheet 10 is suitable for flexible display panel applications. EXAMPLES
[0092] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".
[0093] Example 1 Preparation of Prepolymer Composition In a flask, 0.05 parts by mass of a first photopolymerization initiator (product name "Omnirad184", 1-hydroxycyclohexyl phenyl ketone, IGM Resins) and 0.05 parts by mass of a second photopolymerization initiator (product name "Omnirad819", bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, IGM Resins) were added to a monomer mixture containing 70 parts by mass of n-octyl acrylate (NOAA), 20 parts by mass of n-butyl acrylate (BA), 8 parts by mass of 4-hydroxybutyl acrylate (4HBA), and 2 parts by mass of N-vinyl-2-pyrrolidone (NVP). The mixture was then irradiated with ultraviolet light under a nitrogen atmosphere to polymerize a portion of the monomer components in the mixture to obtain a first prepolymer composition. A black light was used for the ultraviolet irradiation. The ultraviolet irradiation was continued until the viscosity of the composition reached about 20 Pa·s. This viscosity was measured using a Brookfield viscometer with a rotor No. 5 at a rotor speed of 10 rpm at a temperature of 30° C. (The same applies to the viscosity described below.) The obtained prepolymer composition was a partial polymer containing a photopolymerized product and a monomer component that had not undergone a polymerization reaction (residual monomer).
[0094] Preparation of Pressure-Sensitive Adhesive Composition 100 parts by mass of the first prepolymer composition, 0.055 parts by mass of dipentaerythritol hexaacrylate (DPHA) as a crosslinking agent, 0.3 parts by mass of a silane coupling agent (trade name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.01 parts by mass of a photopolymerization initiator (Omnirad819) were mixed together to prepare adhesive composition C1. The composition of adhesive composition C1 is shown in Table 1. In Table 1, the units of each numerical value expressing the composition are relative "parts by mass".
[0095] <Formation of Pressure-Sensitive Adhesive Layer> The long first release liner was run in the length direction of the release liner while the coating process, the first lamination process, the photocuring process, the peeling process, the heating process, and the second lamination process were carried out in sequence (roll-to-roll process). The first release liner was a polyethylene terephthalate (PET) film with a thickness of 75 μm, one side of which was treated with a silicone release agent. The running speed of the first release liner was 4.0 m / min.
[0096] In the coating step, the pressure-sensitive adhesive composition C1 was applied to the release-treated surface of the first release liner by a roll coater to form a coating film. In the first lamination step, the release-treated surface of the second release liner, one side of which was treated with a silicone release agent, was laminated to the coating film on the first release liner. The second release liner was a long PET film (75 μm thick) with one side treated with a silicone release agent.
[0097] In the photocuring process, the coating film between the release liners was irradiated with ultraviolet (UV) rays to photocure the coating film and form a 25 μm thick adhesive layer. In the UV irradiation, a black light was used as the irradiation light source, and the irradiation intensity was about 6.5 mW / cm. 2 The cumulative irradiation dose was 390 mJ / cm 2 It was decided.
[0098] In the peeling process, the second release liner was peeled off from the adhesive layer on the first release liner. In the heating process, first heating and second heating were carried out sequentially in a hot air heating oven to dry the adhesive layer on the first release liner. In the first heating, the heating temperature (first heating temperature) was set to 120°C. In the second heating, the heating temperature (second heating temperature) was set to 90°C.
[0099] In the second lamination process, the release-treated surface of a third release liner, one side of which had been treated with a silicone release agent, was laminated to the adhesive layer on the first release liner. The third release liner was a long PET film (75 μm thick) with one side treated with a silicone release agent.
[0100] In this manner, an optical adhesive sheet (thickness: 25 μm) of Example 1 with double-sided release liners was produced.
[0101] Example 2 An optical adhesive sheet of Example 2 was produced in the same manner as the optical adhesive sheet of Example 1, except for the following: In the heating step, the second heating was not performed.
[0102] Example 3 An optical adhesive sheet of Example 3 was produced in the same manner as the optical adhesive sheet of Example 1, except for the following: In the heating step, the first heating temperature was set to 110° C., and the second heating was not performed.
[0103] Example 4 Preparation of Prepolymer Composition In a flask, 0.05 parts by mass of a first photopolymerization initiator (Omnirad184) and 0.05 parts by mass of 2,2-dimethoxy-1,2-diphenylethan-1-one (trade name "Omnirad651", manufactured by IGM Resins) as a second photopolymerization initiator were added to a monomer mixture containing 60 parts by mass of 2-ethylhexyl acrylate (2EHA), 36 parts by mass of lauryl acrylate (LA), 2 parts by mass of 4-hydroxybutyl acrylate (4HBA), and 2 parts by mass of N-vinyl-2-pyrrolidone (NVP). The mixture was then irradiated with ultraviolet light under a nitrogen atmosphere to polymerize a portion of the monomer components in the mixture, thereby obtaining a second prepolymer composition (containing monomer components that have not undergone a polymerization reaction) with a polymerization rate of about 10%. The ultraviolet light irradiation was continued until the viscosity of the composition reached about 20 Pa·s.
[0104] Preparation of Pressure-Sensitive Adhesive Composition 100 parts by mass of the second prepolymer composition, 0.08 parts by mass of 1,6-hexanediol diacrylate (HDDA) as a crosslinking agent, 0.3 parts by mass of a silane coupling agent (trade name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.01 parts by mass of a photopolymerization initiator (Omnirad819) were mixed together to prepare adhesive composition C2.
[0105] <Formation of Pressure-Sensitive Adhesive Layer> The long first release liner was run in the length direction of the release liner, and the coating step, the first bonding step, the photocuring step, the peeling step, the heating step, and the second bonding step were carried out in sequence (roll-to-roll process). Specifically, the coating step to the second bonding step were the same as the coating step to the second bonding step described above in relation to the manufacturing method of the optical adhesive sheet of Example 1.
[0106] In this manner, a pressure-sensitive adhesive sheet (thickness: 50 μm) with double-sided release liners of Example 4 was produced.
[0107] Comparative Example 1 The optical adhesive sheet of Comparative Example 1 was produced in the same manner as the optical adhesive sheet of Example 1, except for the following: In the roll-to-roll process, the peeling step, heating step, and second lamination step were not performed after the photocuring step.
[0108] Comparative Example 2 The optical adhesive sheet of Comparative Example 2 was produced in the same manner as the optical adhesive sheet of Example 1, except for the following: In the roll-to-roll process, the thickness of the adhesive layer formed between the release liners by the coating step, the first lamination step, and the photocuring step was 50 μm, and the peeling step, heating step, and second lamination step were not performed after the photocuring step.
[0109] Comparative Example 3 The optical adhesive sheet of Comparative Example 3 was produced in the same manner as the optical adhesive sheet of Example 1, except for the following: In the roll-to-roll process, the running speed of the first release liner was 8.0 m / min, and after the photocuring step, the peeling step, heating step, and second lamination step were not performed.
[0110] <Total light transmittance> For each of the optical pressure-sensitive adhesive sheets in Examples 1 to 4 and Comparative Examples 1 to 3, the total light transmittance was measured as follows.
[0111] First, a sample for measurement was prepared. Specifically, after peeling off the third release liner from the optical adhesive sheet, the exposed surface of the optical adhesive sheet was attached to alkali-free glass (manufactured by Matsunami Glass Co., Ltd.), and the first release liner was peeled off from the optical adhesive sheet on the glass. This resulted in a sample for measurement. Next, the total light transmittance of the sample was measured in accordance with JIS K7136 (2000) using a haze meter "HM-150N" manufactured by Murakami Color Research Laboratory Co., Ltd. In addition, in this measurement, the measurement results obtained by measuring only the alkali-free glass under the same conditions were used as the baseline. The total light transmittance (%) of each optical adhesive sheet is shown in Table 1.
[0112] <Shear storage modulus> The dynamic viscoelasticity was measured for each of the optical adhesive sheets in Examples 1 to 4 and Comparative Examples 1 to 3. Specifically, the measurement was as follows.
[0113] First, a required number of measurement samples were prepared for each optical adhesive sheet. Specifically, a required number of optical adhesive sheets cut from the optical adhesive sheet were laminated together to prepare a sample sheet with a thickness of about 2 mm. Next, this sheet was punched out to obtain a cylindrical pellet (diameter 7.9 mm) as a measurement sample.
[0114] The measurement sample was then fixed to a parallel plate fixture with a diameter of 7.9 mm and subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (name: Advanced Rheometric Expansion System (ARES), manufactured by Rheometric Scientific). In this measurement, the measurement mode was shear mode, the measurement temperature range was -50°C to 150°C, the heating rate was 5°C / min, and the frequency was 1 Hz. From the measurement results, the shear storage modulus (kPa) at the specified temperatures (-20°C, 25°C, 60°C) was read. The values are shown in Table 1.
[0115] <Cd ion concentration> The Cd ion concentration was measured for each of the optical adhesive sheets in Examples 1 to 4 and Comparative Examples 1 to 3. Specifically, the measurement was as follows.
[0116] First, a sample piece was cut out from the optical adhesive sheet. Next, the sample piece was decomposed with acid, and the cations in the acid decomposition product were filtered and extracted. The type and amount of the cations were measured by inductively coupled plasma optical emission spectrometry (ICP-OES). The measured Cd ion concentration (mg / kg) is shown in Table 1.
[0117] <Moisture permeability> The moisture permeability was examined for each of the optical adhesive sheets of Examples 1 to 4 and Comparative Examples 1 to 3. Specifically, the results are as follows.
[0118] First, the optical adhesive sheet with double-sided release liners was left to stand for 3 days in an atmosphere with a temperature of 23°C and a relative humidity of 55%. This adjusted the condition of the adhesive sheet. Next, one of the release liners was peeled off from the optical adhesive sheet, and the exposed surface was then covered with a 25 μm-thick triacetyl cellulose (TAC) film (moisture permeability: 1070 g / m 2 The other release liner was then peeled off from the optical adhesive sheet on the TAC film. This gave a sample film for moisture permeability measurement.
[0119] Next, the moisture permeability in the thickness direction of the optical adhesive sheet was measured in accordance with the moisture permeability test (cup method) of JIS Z0208. Specifically, first, a predetermined amount of calcium chloride weighed in advance was placed in a test cup (an aluminum cup having a circular opening with a diameter of 30 mm, used in the cup method of JIS Z0208), and the opening of the cup was blocked with a sample film. The area of the sample film blocking the opening of the cup corresponds to the area of a circle with a diameter of 30 mm. Next, the cup with the sample film was placed in a constant temperature and humidity chamber at a temperature of 40°C and a relative humidity of 92%, and left for 24 hours. Next, the calcium chloride taken out of the cup was weighed. The increased mass (g) of calcium chloride was multiplied by the area (m 2 The value was divided by the moisture permeability (g / m2) of the optical pressure-sensitive adhesive sheet. 2 ·24h) is shown in Table 1. The moisture permeability obtained in this manner is the moisture permeability of the optical adhesive sheet with the TAC film, but since the moisture permeability of the TAC film is sufficiently greater than that of the optical adhesive sheet, the moisture permeability of the sample film was regarded as the moisture permeability of the optical adhesive sheet.
[0120] <Evaluation of iodide ion permeability> For each of the optical adhesive sheets in Examples 1 to 4 and Comparative Examples 1 to 3, the following first high temperature and humidity test and second high temperature and humidity test were carried out to examine the permeability of iodide ions.
[0121] First high temperature and high humidity test: First, a polarizing film with a retardation layer having a protective layer of 20 μm, a first adhesive layer of 1 μm, a polarizer film of 5 μm, a second adhesive layer of 1 μm, a first retardation layer of 3 μm, a third adhesive layer of 1 μm, and a second retardation layer of 4 μm in this order in the thickness direction is prepared. This polarizing film with a retardation layer was produced as described below. Next, the first adhesive surface of the optical adhesive sheet was attached to the second retardation layer side of the polarizing film to obtain a film with an adhesive layer. Next, a film piece with an adhesive layer having a size of 40 mm x 40 mm was cut out from the film with the adhesive layer. Next, the adhesive layer side of the film piece with the adhesive layer was attached to the center of a square aluminum plate (product name "Cerapeel DMS-X42", aluminum reflector, manufactured by Toray Film Processing Co., Ltd.) of 45 mm x 50 mm x 1 mm in plan view to obtain a laminate. In this laminate, the four sides of the aluminum plate and the four sides of the film with the adhesive layer are parallel. Next, the initial resistance value R0 of the aluminum plate in the laminate (aluminum plate / adhesive layer derived from optical adhesive sheet / polarized film) was measured. Specifically, the sheet resistance of the aluminum plate surface in the laminate was measured by an eddy current method in accordance with JIS Z 2316 using a non-contact resistance measuring device NC-80LINE manufactured by Napson Co., Ltd. (the same applies to the measurement of resistance values R1 and R2 described below). Next, the laminate was autoclaved for 15 minutes under conditions of a temperature of 50°C and a pressure of 0.5 MPa. Next, the laminate was left to stand at room temperature for 1 hour. Next, the laminate was left to stand in a high-temperature and high-humidity environment for 120 hours under conditions of a temperature of 85°C and a relative humidity of 85%. Next, the resistance value R1 of the aluminum plate in the laminate was measured. Next, the first change rate (R1 / R0) of the resistance value R1 relative to the initial resistance value R0 was calculated. The results are shown in Table 1.
[0122] Second high temperature and high humidity test: First, the laminate (aluminum plate / adhesive layer derived from optical adhesive sheet / polarizing film) after the first high temperature and high humidity test was left in a high temperature and high humidity environment for 120 hours under conditions of a temperature of 85°C and a relative humidity of 85%. Next, the resistance value R2 of the aluminum plate in the laminate was measured. Next, the second change rate (R2 / R0) of the resistance value R2 relative to the initial resistance value R0 was calculated. The results are shown in Table 1.
[0123] The above-mentioned polarizing film with a retardation layer was produced as follows.
[0124] Formation of Polarizer Film An amorphous isophthalic acid copolymerized polyethylene terephthalate film (thickness 100 μm, Tg 75° C., water absorption rate 0.75%) was prepared as a long thermoplastic base film. One side of this film was corona-treated in advance. In addition, 100 parts by mass of polyvinyl alcohol (PVA) resin was mixed with water to prepare a PVA resin aqueous solution. The PVA resin was a mixture of 90 parts by mass of PVA (polymerization degree 4200, saponification degree 99.2 mol%) and 10 parts by mass of acetoacetyl-modified PVA (product name "GOHSEFYMER Z200", polymerization degree 1200, acetoacetyl-modification degree 4.6%, saponification degree 99.0 mol% or more, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.).
[0125] A PVA resin aqueous solution was applied to the corona-treated surface of the base film at 25° C. to form a coating film. The coating film was then dried at 25° C. to form a PVA resin film with a thickness of 13 μm on the base film. This resulted in a long laminate (base film / PVA resin film).
[0126] Next, the laminate was uniaxially stretched (auxiliary air stretching process) in an oven at 130° C. In this stretching process, the laminate was stretched in the longitudinal direction between rolls rotating at different speeds, and the stretching ratio was 2.4 times.
[0127] Next, the laminate was immersed for 30 seconds in an insolubilizing bath (insolubilizing treatment) at a temperature of 40° C. The insolubilizing bath was an aqueous solution of boric acid prepared by mixing 100 parts by mass of water and 4 parts by mass of boric acid.
[0128] Next, the laminate was immersed in a dye bath at a temperature of 30° C. (dyeing treatment). The dye bath was an aqueous iodine solution prepared by mixing 100 parts by mass of water, 1 part by mass of solid iodine, and 7 parts by mass of potassium iodide. Specifically, in the dyeing treatment, the laminate was immersed in the dye bath so that the single-piece transmittance of the PVA resin film on the base film in the laminate was 42% or more.
[0129] Next, the laminate was immersed for 35 seconds in a crosslinking bath (crosslinking treatment) at a temperature of 40° C. The crosslinking bath was an aqueous boric acid solution prepared by mixing 100 parts by mass of water, 3 parts by mass of potassium iodide, and 5 parts by mass of boric acid.
[0130] Next, the laminate was uniaxially stretched (underwater stretching treatment) in an aqueous boric acid solution (boric acid concentration: 4% by mass, potassium iodide concentration: 5% by mass) at a temperature of 70° C. In this stretching treatment, the laminate was stretched in the longitudinal direction between rolls rotating at different speeds, and the stretching ratio was 5.5 times.
[0131] Next, the laminate was immersed in a cleaning bath (cleaning treatment) at a temperature of 20° C. The cleaning bath was an aqueous solution prepared by mixing 100 parts by mass of water and 4 parts by mass of potassium iodide.
[0132] Next, the substrate film side of the laminate was dried in an oven at 60° C. As a result, a polarizer film having a thickness of 5 μm was formed on the substrate film as a PVA resin film that had been dyed with iodine and then uniaxially stretched.
[0133] Preparation of Polarizing Film Next, an acrylic film (product name "RV-20UB", thickness 20 μm, manufactured by Toyo Kohan Co., Ltd.) was attached as a protective film to the exposed surface of the polarizer film on the substrate film (the surface opposite to the substrate film) via an ultraviolet-curing adhesive. Specifically, first, an ultraviolet-curing adhesive was applied to the exposed surface of the polarizer film on the substrate film to form an adhesive coating film (thickness 1 μm), and then the polarizer film and the protective film were attached to each other via the adhesive coating film using a rolling machine. Next, the adhesive coating film between the protective film and the polarizer film was irradiated with ultraviolet light from the protective film side to harden the adhesive coating film. This allowed the protective film to be bonded to the polarizer film. This resulted in a polarizing film having a laminated structure of a protective film (protective layer), a first adhesive layer having a thickness of 1 μm, and a polarizer film (the substrate film was attached to the polarizer film side).
[0134] <Formation of the first retardation layer> First, 55 parts by mass of a first compound represented by the following chemical formula (I), 25 parts by mass of a second compound represented by the following chemical formula (II), and 20 parts by mass of a third compound represented by the following chemical formula (III) were added to 400 parts by mass of cyclopentanone (CPN), and then the mixture was stirred at 60°C to dissolve each compound in CPN. This resulted in a first solution. Next, the first solution was returned to room temperature. Next, 3 parts by mass of a photopolymerization initiator (product name "Irgacure 907", manufactured by BASF Japan Ltd.), 0.2 parts by mass of a surfactant (product name "Megafac F-554", manufactured by DIC Corporation), and 0.1 parts by mass of p-methoxyphenol (MEHQ) as an antioxidant were added to the first solution, and the mixture was stirred to obtain a second solution. This second solution was transparent and uniform. Next, the second solution was filtered through a membrane filter to obtain a polymerizable composition. The mesh size of the membrane filter was 0.20 μm.
[0135] [ka]
[0136] [ka]
[0137] [ka]
[0138] On the other hand, a polyimide solution for an alignment film was applied to a glass substrate having a thickness of 0.7 mm by spin coating to form a coating film. Next, the coating film on the glass substrate was dried by heating at 100°C for 10 minutes, and then baked by heating at 200°C for 60 minutes to solidify. Next, the solidified coating film was rubbed with a commercially available rubbing device (alignment treatment). The rubbing direction was set such that, after bonding the first liquid crystal alignment solidified layer described below to the polarizer film side of the above-mentioned polarizing film, the alignment direction of the liquid crystal compound in the layer was 15° clockwise with respect to the absorption axis of the polarizer film as viewed from the polarizing film side. In this way, an alignment film was formed on the glass substrate. The exposed surface of this alignment film (the surface opposite to the glass substrate) was the alignment treatment surface.
[0139] Next, the above-mentioned polymerizable composition was applied to the alignment treatment surface of the glass substrate by spin coating to form a coating film. Next, this coating film was dried by heating at 100°C for 2 minutes to form a liquid crystal layer. In this liquid crystal layer, the liquid crystal compound is aligned along the rubbing direction of the alignment treatment surface of the alignment film. Next, the liquid crystal layer was irradiated with ultraviolet light to photo-cure the liquid crystal layer, thereby forming a first liquid crystal alignment solidified layer (first retardation layer) having a thickness of 3 μm. For ultraviolet light irradiation, a high-pressure mercury lamp was used as the irradiation light source, and the irradiation intensity was 30 mW / cm. 2 The irradiation time was 30 seconds. The first liquid crystal alignment solidified layer had an in-plane retardation Re(550) of 130 nm at a wavelength of 550 nm. The ratio of the in-plane retardation Re(450) of the first liquid crystal alignment solidified layer at a wavelength of 450 nm to the in-plane retardation Re(550) was 0.851, indicating a reverse dispersion wavelength characteristic. Such a first retardation layer can function as a λ / 4 plate.
[0140] <Formation of the second retardation layer> First, 20 parts by mass of a side-chain liquid crystal polymer (weight average molecular weight 5000) represented by the following chemical formula (IV), 80 parts by mass of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (trade name "Paliocolor LC242", manufactured by BASF), and 5 parts by mass of a photopolymerization initiator (trade name "Irgacure 907", manufactured by BASF Japan) were dissolved in 200 parts by mass of cyclopentanone to prepare a liquid crystal composition. In chemical formula (IV), the numbers 65 and 35 indicate the mol% of the monomer unit, and the side-chain liquid crystal polymer is conveniently represented as a block polymer.
[0141] [ka]
[0142] On the other hand, the above-mentioned liquid crystal composition was applied to the alignment treatment surface of a polyethylene terephthalate (PET) film (thickness 38 μm) having a vertically aligned alignment treatment surface by a bar coater to form a coating film. Next, the coating film on the PET film was dried by heating at 80° C. for 4 minutes to form a liquid crystal layer. This liquid crystal layer is vertically aligned. Next, the liquid crystal layer on the PET film was irradiated with ultraviolet light to photo-cure the liquid crystal layer, thereby forming a second liquid crystal alignment solidified layer (second retardation layer) having a thickness of 4 μm. For ultraviolet light irradiation, a high-pressure mercury lamp was used as the irradiation light source, and the illuminance was set to 30 mW / cm. 2 The irradiation time was 30 seconds. It was confirmed that this second liquid crystal alignment solidified layer had a refractive index characteristic of nz>nx=ny.
[0143] <Formation of polarizing film with retardation layer> First, the substrate film was peeled off from the polarizing film (polarizer film / protective film), and then an ultraviolet-curable adhesive was applied to the exposed polarizer film to form an adhesive coating (1 μm thick), and then the polarizer film and the first liquid crystal alignment solidified layer on the glass substrate were bonded together via the adhesive coating. At this time, the polarizer film was bonded together such that the angle between the absorption axis of the polarizer film and the alignment direction (slow axis) of the liquid crystal compound in the first liquid crystal alignment solidified layer was 15°. Next, the adhesive coating between the polarizer film and the first liquid crystal alignment solidified layer was irradiated with ultraviolet light from the PET film side to harden the adhesive coating. As a result, the first liquid crystal alignment solidified layer was bonded to the polarizer film. After that, the glass substrate was peeled off from the first liquid crystal alignment solidified layer. As a result, an intermediate laminate having a laminated structure of the polarizing film, the second adhesive layer, and the first liquid crystal alignment solidified layer (first retardation layer) was obtained.
[0144] Next, the following adhesive composition was applied to the exposed surface of the first liquid crystal alignment solidified layer of the intermediate laminate to form an adhesive coating film (thickness 1 μm), and then the first liquid crystal alignment solidified layer and the second liquid crystal alignment solidified layer on the PET film were bonded together via the adhesive coating film. Next, the adhesive coating film between the first and second liquid crystal alignment solidified layers was irradiated with ultraviolet light from the PET film side to harden the adhesive coating film. As a result, the second liquid crystal alignment solidified layer was bonded to the first liquid crystal alignment solidified layer. After that, the PET film was peeled off from the second liquid crystal alignment solidified layer. As a result, a retardation layer-attached polarizing film was obtained having a laminated structure of a protective film (thickness 20 μm), a first adhesive layer (thickness 1 μm), a polarizer film (thickness 5 μm), a second adhesive layer (thickness 1 μm), a first liquid crystal alignment solidified layer (first retardation layer with a thickness of 3 μm), a third adhesive layer (thickness 1 μm), and a second liquid crystal alignment solidified layer (second retardation layer with a thickness of 4 μm). The thickness of this retardation layer-attached polarizing film was 35 μm.
[0145] Preparation of Adhesive Composition 20 parts by mass of acryloylmorpholine (product name "ACMO", manufactured by KJ Chemicals), 10 parts by mass of unsaturated fatty acid hydroxyalkyl ester modified epsilon-caprolactone (product name "PLACCEL FA1DDM", manufactured by Daicel Corporation), 60 parts by mass of a mixture of fluorene-based acrylate and reactive acrylate (product name "Oxol EA-F5710", manufactured by Osaka Gas Chemicals Co., Ltd.), 5 parts by mass of acrylic polymer (product name "ARUFON UP-1190", manufactured by Toa Gosei Co., Ltd.), 3 parts by mass of a first photopolymerization initiator (product name "Omnirad907", manufactured by IGM Resins Co., Ltd.), and 2 parts by mass of a second photopolymerization initiator (product name "KAYACURE DETX-S", manufactured by Nippon Kayaku Co., Ltd.) were mixed at 25°C for 1 hour to prepare an adhesive composition.
[0146] [Table 1] [Explanation of symbols]
[0147] 10 Adhesive sheet (optical adhesive sheet) H Thickness direction 11 Adhesive surface (1st adhesive surface) 12 Adhesive surface (second adhesive surface) L1, L2 Release liner
Claims
1. An optical adhesive sheet having a first adhesive surface and a second adhesive surface opposite to the first adhesive surface, The optical adhesive sheet is a solventless adhesive sheet containing a photopolymerized polymer as a base polymer, The optical adhesive sheet has a shear storage modulus of 100 kPa or less at 25 ° C., The first rate of change in resistance of the aluminum plate in the first high temperature and high humidity test (R 1 / R 0 ) is 120% or less. First high temperature and high humidity test: First, a polarizing film with a retardation layer having a thickness of 20 μm, a first adhesive layer with a thickness of 1 μm, a polarizer film with a thickness of 5 μm, a second adhesive layer with a thickness of 1 μm, a first retardation layer with a thickness of 3 μm, a third adhesive layer with a thickness of 1 μm, and a second retardation layer with a thickness of 4 μm in this order in the thickness direction is prepared. Next, the first adhesive surface of the optical adhesive sheet is bonded to the second retardation layer side of the polarizing film with the retardation layer to obtain a film with an adhesive layer. Next, a piece of film with an adhesive layer having a size of 40 mm x 40 mm is cut out from the film with an adhesive layer. Next, the adhesive layer side of the film piece with the adhesive layer is attached to the center of a square aluminum plate of 45 mm × 50 mm × 1 mm in plan view to obtain a laminate. Next, the initial resistance value R 0 Next, the laminate is autoclaved for 15 minutes under conditions of a temperature of 50° C. and a pressure of 0.5 MPa. Next, the laminate is left to stand at room temperature for 1 hour. Next, the laminate is left to stand in a high-temperature and high-humidity environment for 120 hours under conditions of a temperature of 85° C. and a relative humidity of 85%. Next, the resistance value R of the aluminum plate in the laminate is measured. 1 Next, measure the initial resistance R 0 Resistance value R 1 The first rate of change (R 1 / R 0 ) is calculated.
2. The second change rate (R 2 / R 0 2. The optical adhesive sheet according to claim 1, wherein the optical adhesive sheet has a refractive index of 150% or less. Second high temperature and high humidity test: First, the laminate after the first high temperature and high humidity test is left in a high temperature and high humidity environment for 120 hours under conditions of a temperature of 85° C. and a relative humidity of 85%. Next, the resistance value R 2 Next, measure the initial resistance R 0 Resistance value R 2 The second rate of change (R 2 / R 0 ) is calculated.
3. The optical adhesive sheet according to claim 1, having a shear storage modulus of 200 kPa or less at -20 ° C.
4. Moisture permeability measured at 40°C and 92% relative humidity is 700 g / m 2 The optical adhesive sheet according to claim 1, wherein the durability is 24 hours or less.
5. The optical adhesive sheet according to claim 1 , wherein the Cd ion content is 5 mg / kg or less.
Citation Information
Patent Citations
Adhesive sheet
JP2018111754A